HYDROCHEMICAL CHARACTERISATION OF A COASTAL AQUIFER AT THE GERMAN NORTH-SEA COAST - PANTELEIT, B. (Hidrogeologia, 2003)
In an ongoing project a Coastal Aquifer Testfield (CAT-Field) was installed for hydrological investigations at the German North Sea coast. Because of the partly coarse grained sediments the region seems to be suitable and may be interesting for future groundwater exploitation. To determine their possible influences is the aim of an interdisciplinary project. For the interpretation of the geochemical processes occurring in the salt- freshwater transition zone and during salinization, field data are compared with results from laboratory experiments and numerical calculations. Different types of groundwater are characterised by their geochemical pattern. Possible mechanisms for the formation of present NaHCO3 waters are Calcite precipitation and exchanger reactions during refreshening of the aquifer. These are briefly discussed with respect to results of column experiments, a twodimensional flow chamber experiment and their geochemical modelling with the computer programs PHREEQC (Parkhurst and Appelo, 1999) and Processing SHEMAT (Kühn and Chiang, 2000).